DUAL MOBILITY CUP CEMENTED INTO POROUS TRABECULAR METAL SHELL DURING REVISION TOTAL HIP ARTHROPLASTY - Maksim Zagorov; Svetoslav Dobrilov; Kalin Mihov (Peytchinski Publishing, 2023)
Revision total hip arthroplasty (RTHA) is a challenging procedure when we speak about acetabular defects and recurrent instability. There are multiple reasons like the number of previous revisions, implant position, bone quality, patient characteristics and etc. Managing acetabular defects with porous trabecular metal augments has excellent survivorship, but when addressing instability, there are some unsolved issues. Management options include the use of large femoral heads, constrained acetabular liners, and dual mobility cups (DMC). These cups have increased jump distance and reduced likelihood of dislocation while not relying on locking mechanisms, therefore are the preferred option in RTHA. We present single-center series of 13 patients undergoing revision THA with a specific DMC cemented into a newly implanted or well-fixed trabecular metal (TM) revision shell. All patients underwent cementation of a single specific cemented DMC design (Novae Stick, SERF, Decines, France) in a Trabecular Metal Revision Shell (Zimmer Biomet, Warsaw, IN, US). The mean follow-up is 15,2 months, and there were no dislocations of the implanted DM cups. The mean HHS improved significantly from 35.9 (range 15-80) preoperatively to 80.1 (range 64-93) postoperatively (p = 0.001). The results of this small clinical series demonstrate that cementing a DMC in a well-fixed TM revision shell leads to no dislocation or dissociation of the cement interface and acetabular construct loosening in the short term